EDUKASI TERAPI DISTRAKSI AUDIOVISUAL SEBAGAI UPAYA PENCEGAHAN TRAUMA INJEKSI PADA ANAK DI DUSUN II DESA SIDODADI KECAMATAN BIRU-BIRU KABUPATEN DELI SERDANG - Barus, Dewi Tiansa; Ginting, Daniel Suranta; Silalahi, Rini Debora; Arianto, Adi; Purba, Rentawati (Jurnal Pengabdian Masyarakat Putri Hijau, 2025)
Injection trauma in children is a common problem that can lead to anxiety, fear, and refusal of health care procedures in the future. One effective non-pharmacological approach to preventing injection trauma is audiovisual distraction therapy. This community service activity aimed to provide education on audiovisual distraction therapy as an effort to prevent injection trauma in children in Hamlet II, Sidodadi Village, Biru-Biru Subdistrict, Deli Serdang Regency. The implementation methods included health education sessions, demonstrations on the use of audiovisual media, and interactive discussions with children and parents. The media used consisted of educational videos and animations designed to capture children’s attention during injection procedures. The results of the activity showed an increase in parents’ knowledge and positive responses from children, as indicated by reduced anxiety and fear during injection simulations. Audiovisual distraction therapy education has proven to be a simple, effective, and easily applicable alternative intervention for both health workers and parents in preventing injection trauma in children. It is expected that this activity will improve the quality of pediatric health services and help create positive experiences during medical procedures.